Mo‐Doped Sulfur‐Vacancy‐Rich V1.11S2 Nanosheets for Efficient Hydrogen Evolution. Issue 23 (17th June 2022) - Chen, Qiuyue; An, Xuguang; Wu, Xiaoqiang; Zhang, Jing; Yao, Weitang; Sun, Chenghua; Wang, Qingyuan; Kong, Qingquan
Abstract: High‐performance low‐cost hydrogen evolution electrocatalysts are urgently demanded for hydrogen production by water splitting. Herein, we report that an efficient defect engineering strategy, NaBH4 treatment, was employed to promote the HER activity of pre‐synthesized Mo‐doped V1.11 S2 nanosheets. The abundant sulfur vacancies enable Mo‐doped V1.11 S2 petaloid nanosheets with a low overpotential of 160 mV and a small Tafel slope of 46.2 mV dec −1 at 10 mA cm −2 to drive the HER, as well as excellent long‐term stability in 0.5 mol L −1 H2 SO4 . The outstanding electrocatalytic performance can be attributed to the large electrochemical surface area and low charge transfer resistance. Abstract : Through an efficient defect engineering strategy, sulfur vacancies were successfully introduced on the pre‐synthesized Mo‐doped V1.11 S2 nanosheets, which greatly enhanced the HER activity of the Mo‐doped V1.11 S2 material. Optimized Mo‐doped V1.11 S2 petaloid nanosheets have a low overpotential of 160 mV and a small Tafel slope of 46.2 mV dec −1 at 10 mA cm −2 to drive the HER.